Method for testing scorching resistance of peroxide crosslinked polyethylene insulating material
The torque and time change curve of peroxide crosslinked polyethylene insulating material was tested by rotor-free vulcanizer, and the anti-coke performance evaluation index was established, which solved the problem of lack of anti-coke performance evaluation method in the existing technology at constant temperature, and realized the problem of the lack of anti-coke performance evaluation method in the current technology. Intuitive and convenient evaluation of the material's anti-coke performance.
Patent Information
- Application Number
- CN202411740953.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-11
AI Technical Summary
At this stage, there is a lack of suitable methods to evaluate the scorching resistance of peroxide crosslinked polyethylene materials at constant temperatures, which leads to frequent scorching problems in cable production and affects cable quality.
The rotor-free vulcanizer tests the torque and time change curves of peroxide crosslinked polyethylene insulating materials at specific temperatures, establishes a calculation formula for anti-coking performance evaluation index, and uses the gel content as the basis for scorching. Determine the scorch torque and scorch time, and judge the material's anti-sorbing performance.
Provides an intuitive and convenient method to evaluate the anti-coke performance of peroxide crosslinked polyethylene insulating materials, fills the gap in the existing technology that lacks anti-coke performance evaluation methods at constant temperature, and helps material R&D personnel provide Reliable scorch-resistant data support.
Smart Images

Figure CN119414006A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electric wires and cables, and relates to a test of the scorch resistance of cable materials, and in particular to a method for testing the scorch resistance of peroxide cross-linked polyethylene insulation materials. Background Art
[0002] With the rapid economic development and the continuous advancement of urbanization, new requirements have been put forward for the quality of power cables. In order to improve the efficiency and quality of power transmission, the voltage level of power cables has been continuously improved, and the demand for cross-linked polyethylene insulation materials for cables with higher voltage levels has greatly increased. In addition, the extrusion distance and time of the cable insulation production process have become longer, so the requirements for the scorch resistance of cable insulation extrusion processing have become higher and higher.
[0003] Peroxide cross-linked polyethylene, as a major branch of cross-linked polyethylene, is widely used as an insulating material in the power cable industry. It is a polyethylene resin modified material with good aging resistance, chemical corrosion resistance, and excellent mechanical properties and electrical insulation properties.
[0004] However, this material often encounters some unavoidable problems in cable production, such as the scorch problem, which has the most serious impact on quality. Peroxide cross-linked polyethylene will inevitably produce rubber retention during the cable laying process. These retained rubbers will slowly undergo pre-cross-linking after being heated for a long time until old char is formed, and eventually fall into the normal insulating rubber and enter the cable, which will cause quality problems such as bulging on the cable surface and failure of the breakdown test. Similarly, when the insulation material manufacturer produces the insulation material, it will inevitably produce old char that enters the insulation material particles, which seriously affects the quality. For insulation material manufacturers, there is currently no suitable method to evaluate the scorch resistance of peroxide cross-linked polyethylene materials at a constant temperature. Therefore, a specific method is needed to evaluate the scorch resistance of peroxide cross-linked polyethylene, so as to provide reliable scorch resistance data support for the research and development process of insulation materials with scorch resistance. Summary of the invention
[0005] In order to solve the defect that there is no evaluation method for the anti-scorch performance of peroxide cross-linked polyethylene at a constant temperature at this stage, the present invention provides a method for testing the anti-scorch performance of peroxide cross-linked polyethylene insulation material. The present invention reflects the anti-scorch performance of peroxide cross-linked polyethylene in the form of data, providing more intuitive and convenient help for new product development, performance testing and competitive product analysis of material researchers.
[0006] The invention provides a method for testing the scorch resistance of a peroxide cross-linked polyethylene insulating material. The method comprises: preparing non-cross-linked test samples from peroxide cross-linked polyethylene insulating materials of different formulations, testing a torque-time curve at a specific temperature by a rotorless vulcanizer, establishing a calculation formula for evaluating an anti-scorch performance index, using gel content as a basis for the occurrence of scorch to determine the scorch torque, further determining the scorch point, and determining the scorch time according to the time difference between the minimum torque and the scorch torque, so as to judge the anti-scorch performance of the material.
[0007] As a preferred embodiment of the present invention, the method is specifically as follows: the test sample is subjected to a heating and melting stage in a rotorless vulcanizer device, and the torque reaches the lowest after complete melting, the lowest torque is recorded as Md, and the time point corresponding to the lowest torque is recorded as the melting point Td. The test sample continues to be heated and gradually cross-linked, and the torque generated in real time on the curve is recorded as the real-time torque Mn, and the change between the real-time torque Mn and the lowest torque Md is recorded as ΔN. The torque starts to rise from the lowest torque Md. When the real-time torque of the curve reaches a certain value, the test is stopped, and the torque of the value is recorded as the scorch torque Ms, that is, the material is scorched under the torque, and the time point corresponding to the scorch torque Ms is recorded as the scorch point Ts, and the torque change from the lowest torque Md to the scorch torque Ms is recorded as ΔM, and the time change between the melting point Td and the scorch point Ts is recorded as the scorch time ΔT, thereby obtaining a formula for calculating ΔM, a formula for calculating ΔT, and a formula for calculating ΔN.
[0008] As a preferred solution of the present invention, the formula is: ΔM=Ms-Md, ΔT=Ts-Td and ΔN=Mn-Md; wherein Md is the minimum torque, Ms is the scorch torque, Ts is the time point corresponding to the scorch torque Ms, and Td is the time point corresponding to the minimum torque.
[0009] As a preferred embodiment of the present invention, the scorch time ΔT is used to indicate the scorch resistance of the peroxide cross-linked polyethylene. The larger the ΔT value is, the better the scorch resistance of the material is.
[0010] As a preferred solution of the present invention, the scorch torque Ms is the torque when the cross-linking degree of the test material reaches a gel content of 80%.
[0011] As a preferred solution of the present invention, the peroxide cross-linked polyethylene insulation material comprises a base material LDPE, a cross-linking agent and an antioxidant.
[0012] As a preferred embodiment of the present invention, the peroxide cross-linked polyethylene insulation material further includes an anti-scorch agent or a cross-linking aid.
[0013] As a preferred embodiment of the present invention, the crosslinking agent is DCP or BIPB.
[0014] As a preferred embodiment of the present invention, the test conditions of the rotorless vulcanizer are: mold cavity swing frequency: 1.7 Hz, mold cavity swing amplitude: +0.5° to -0.5°, mold cavity temperature: 135°C, and mold cavity gas pressure: 0.6 MPa.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] 1) The present invention reflects the anti-scorch performance of peroxide cross-linked polyethylene in the form of data, providing more intuitive and convenient help for new product development, performance testing and competitive product analysis for material researchers.
[0017] 2) The method provided by the present invention can intuitively measure the scorch resistance of peroxide cross-linked polyethylene. At the same time, the testing method principle of the present invention is more in line with the actual scorch process of peroxide cross-linked polyethylene insulation in cable processing, that is, constant temperature and basically no shear heat, which makes up for the current situation of the lack of a method for accurately testing the scorch resistance of peroxide cross-linked polyethylene insulation. At the same time, the method of the present invention provides a certain reference value for the scorch performance test of other thermosetting materials.
[0018] 3) The present invention fills the gap in the current method for evaluating the anti-scorch performance of peroxide cross-linked polyethylene at a constant temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 1 is the torque-time curve and ΔT value of Example 1.
[0020] Figure 2 1 is the torque-time curve and ΔT value of Example 2.
[0021] Figure 3 3 is the torque-time curve and ΔT value of Example 3.
[0022] Figure 4 1 is the torque-time curve and ΔT value of Example 4.
[0023] Figure 5 1 is the torque-time curve and ΔT value of Example 5.
[0024] Figure 6 1 and 2 are the torque-time curve and ΔT value of Example 6.
[0025] Figure 7 1 is the torque-time curve and ΔT value of Example 7.
[0026] Figure 8 1 and 2 are the torque-time curve and ΔT value of Example 8.
[0027] Fig. 9: It is the torque-time curve and ΔT value of Example 9.
[0028] Fig.10 10. The torque-time curve and ΔT value of Example 10.
[0029] Fig.11 It is the torque-time curve and ΔT value of the comparison sample. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] The present invention provides a method for testing the scorch resistance of peroxide cross-linked polyethylene insulation materials. The method comprises: preparing non-cross-linked test samples from peroxide cross-linked polyethylene insulation materials of different formulations, testing a torque-time variation curve at a specific temperature by a rotorless vulcanizer, establishing a calculation formula for evaluating the scorch resistance performance, and judging the scorch resistance of the material according to the time variation corresponding to the torque variation.
[0032] Specifically, the test sample goes through the heating and melting stages in the rotorless vulcanizer equipment. After complete melting, the torque reaches the lowest, and the lowest torque is recorded as Md. The time point corresponding to the lowest torque is recorded as the melting point Td. The test sample continues to be heated and gradually cross-linked. The real-time torque generated on the curve is recorded as the real-time torque Mn, and the change between the real-time torque Mn and the lowest torque Md is recorded as ΔN. The torque starts to rise from the lowest torque Md. When the real-time torque of the curve reaches a certain value, the test is stopped, and the torque of this value is recorded as the scorch torque Ms, that is, the material is scorched under this torque, and the time point corresponding to the scorch torque Ms is recorded as the scorch point Ts. The torque change from the lowest torque Md to the scorch torque Ms is recorded as ΔM, and the time change between the melting point Td and the scorch point Ts is recorded as the scorch time ΔT, thereby obtaining the formula for calculating ΔM, the formula for calculating ΔT and the formula for calculating ΔN.
[0033] The formula is: ΔM=Ms-Md, ΔT=Ts-Td and ΔN=Mn-Md; wherein Md is the minimum torque, Ms is the scorch torque, Ts is the time point corresponding to the scorch torque Ms, and Td is the time point corresponding to the minimum torque.
[0034] The minimum torque Md and the time Td corresponding to the minimum torque can be directly read from the curve.
[0035] From the above principle, it can be seen that if you want to get the scorch time ΔT, you need to get the corresponding scorch point Ts. To get Ts, you need to get the torque corresponding to this point, that is, the scorch torque Ms. When Mn=Ms, ΔN=ΔM. Therefore, the present invention focuses on how to determine whether the material is scorched, so as to determine the scorch torque, and then determine the torque change ΔM from the minimum torque to the scorch torque, and then determine the scorch time ΔT.
[0036] The scorch of the material indicates that the material has been cross-linked, so the degree of scorch of the material can be reflected by the degree of cross-linking, which is represented by the gel content. The gel content of the peroxide cross-linked polyethylene insulation material is required to be ≥80%. In the present invention, the 80% gel content is taken as the reference value. Furthermore, it is only necessary to test the torque when the degree of cross-linking of the material reaches a gel content of 80% to be used as the scorch torque Ms.
[0037] Peroxide cross-linked polyethylene is mainly made of low-density polyethylene, peroxide cross-linking agent, antioxidant and other additives through mixing, extrusion and granulation. Among them, the most commonly used antioxidant is antioxidant 300#, and the common peroxide cross-linking agents are DCP (activation energy 155±4kJ / mol) and BIPB (activation energy 161±6kJ / mol). The two cross-linking agents have different thermal decomposition temperatures due to the different activation energies. The higher the activation energy, the higher the thermal decomposition temperature. Therefore, in practical applications, cross-linked polyethylene using BIPB cross-linking agent often shows better scorch resistance during processing. In addition, the addition of antioxidants will also affect the scorch resistance of peroxide cross-linked polyethylene. Taking antioxidant 300# as an example, the common addition amount is 0.05% to 0.3%. The more it is added, the better the scorch resistance performance.
[0038] In order to avoid pre-crosslinking and thus scorching during the processing and cable extrusion and pay-off process of peroxide cross-linked polyethylene insulation, the processing protection temperature is generally around 135°C, that is, pre-crosslinking is likely to occur when the processing temperature exceeds 135°C. However, according to the time-temperature equivalence principle, even if the temperature is kept at 135°C or below, a small part of the rubber will inevitably remain in the extruder head and other parts for a long time to form coke. This greatly increases the risk of long-term startup, requires shortening the startup cycle, and increases the frequency of cleaning, which seriously affects the production efficiency of materials and cables. Therefore, the slower the pre-crosslinking occurs at 135°C, the less likely it is to scorch.
[0039] The rotorless rheometer (MDR for short) is a device used to evaluate the vulcanization characteristics of rubber materials. It has the characteristics of constant temperature and basically no shear heat. It is feasible for some materials that need to test the vulcanization characteristics at a constant temperature.
[0040] The present invention prepares non-crosslinked samples from peroxide cross-linked polyethylene insulation materials of different formulations, and uses MDR to test the torque-time curve at a specific temperature, and the scorch resistance of the material can be determined according to the time variation corresponding to the torque variation.
[0041] The test device used in the present invention is a rotorless vulcanizer with a mold cavity diameter of 40 mm and a mold cavity volume of 4.5 cm 3 , hereinafter referred to as MDR.
[0042] The sample preparation method of the present invention is as follows: taking peroxide cross-linked polyethylene insulation material particles required for testing and placing them in an extruder at 115° C. for extrusion so that the additives in the sample particles are more evenly dispersed, and after the extruded sample strips are cooled, placing them in a flat vulcanizer for tabletting and sample preparation, the tabletting mold thickness is 4 mm, the tabletting temperature is 110° C., preheating and melting for 45 seconds without pressure, pressurizing 10 MPa for exhaust for 45 seconds, and pressurizing to 20 MPa for holding the pressure for 3 minutes after exhausting. After the pressure holding ends, the mold is moved into a cooling vulcanizer, pressurized to 20 MPa for cooling for 3 minutes, and the slices are completely cooled and cut into round sample pieces with a diameter of 35 mm to prepare uncross-linked test samples. The sample surface needs to be flat and smooth, and the sample interior is free of impurities and pores.
[0043] Example
[0044] ΔM test method:
[0045] Take a control sample, make the control sample into the required specifications according to the formula in Table 1 by the above sample preparation method, and then place it in the MDR. The MDR equipment is tested under the following conditions:
[0046] Cavity swing frequency: 1.7Hz;
[0047] Cavity swing range: +0.5° to -0.5°;
[0048] Cavity temperature: 135°C (protective temperature of cross-linked polyethylene insulation during production and cable extrusion);
[0049] Cavity gas pressure: 0.6MPa;
[0050] After the test conditions are met, the control sample is placed in the mold cavity of the MDR equipment for 20 seconds, and the mold is closed immediately to avoid the temperature drop of the mold cavity. The experiment is started and the torque-time curve is obtained.
[0051] As time goes by, the real-time torque is displayed on the curve. When the real-time torque Mn is 0.5 dN·m higher than the minimum torque Md, the experiment is stopped, the sample is taken out, and the center part of the sample is cut off to test the gel content.
[0052] The gel content test method refers to the A.4 test method 2 shown in the Appendix A of the Ministry of Machinery Standard JB / T 10437-2024 "Cross-linked Polyethylene Insulation Materials for Wires and Cables". Repeat the above test operation, and test the gel content of the sample when the real-time torque Mn of the comparison sample is 1.0dN·m, 1.5dN·m, and 2.0dN·m higher than the minimum torque Md. The real-time torque Mn corresponding to the gel content closest to 80% can be used as the scorch torque Ms, at which time Mn = Ms, ΔN = ΔM. See Table 1 for the comparison sample formula, and see Table 2 for the gel content data at different torque values.
[0053] Table 1. Comparative sample formulations
[0054] raw materials Base material LDPE Crosslinking agent DCP Antioxidant 300# Comparative sample formulation (wt%) 97.8 2.0 0.2
[0055] *Description of the comparative sample formula: The comparative sample formula is the most commonly used formula in the current peroxide cross-linked polyethylene insulation material market. Therefore, this formula is selected as the comparative sample in the present invention to test its ΔM. At the same time, the test formula will be compared and verified with the ΔM of this formula as the benchmark value. That is, the time change ΔT (scorch time) of other test formulas to reach ΔM is greater than the ΔT of the comparative sample, which means that the anti-scorch performance is better than that of the comparative sample, otherwise it is worse.
[0056] Table 2. Gel content of the comparison samples at different ΔN torque values
[0057] ΔN(dN·m) 0.5 1.0 1.5 2.0 Gel content (%) 52.9 80.2 83.0 84.7
[0058] It can be seen from Table 2 that when the real-time torque Mn of the control sample is 1.0 dN·m higher than the minimum torque Md, the gel content of the control sample is closest to 80%, reaching 80.2%, which means that the material has been scorched as mentioned above, and the torque has reached the scorch torque Ms, that is, Mn=Ms, ΔN=ΔM, and ΔM=1.0 dN·m, it can be determined that the material has been scorched.
[0059] The formulas of Examples 1 to 10 are the formulas of Experimental Samples 1 to 10, and the experimental formulas are shown in Table 3.
[0060] Table 3. Experimental formulation design
[0061]
[0062] The torque-time curves corresponding to the experimental samples 1 to 10 are as follows: Figures 1 to 10 As shown, the corresponding torque-time curve of the comparison sample is as follows Fig.11 shown.
[0063] The numerical values of the scorch time ΔT in the above embodiments are summarized in Table 4:
[0064] Table 4. Summary of scorch time ΔT values for different examples
[0065]
[0066] Combining the corresponding relationship between the formula design and the scorch time ΔT of the above embodiments, it can be seen that the scorch time under different types of additives and different addition amounts also conforms to the formula design, and also corresponds to the different scorch times of cross-linking agents with different activation energies mentioned above. Comparing Example 1 and Example 2, it can be seen that the anti-scorch performance of the formula is significantly improved after the addition of antioxidant 300#; comparing Example 1 and Example 3, it can be seen that the addition amount of antioxidant 300# affects the scorch resistance of the formula, and the scorch resistance of the formula with more 300# added is more prominent; comparing Example 1 and Example 4, it can be seen that the scorch resistance of the formula is significantly improved after the addition of the anti-scorch agent, indicating that the anti-scorch agent has exerted an anti-scorch effect; comparing Example 5 and Example 6, it can also be seen that the addition of the anti-scorch agent improves the anti-scorch performance of the material; comparing Example 7 and Example 8, it can be seen that the scorch resistance of the material deteriorates after the addition of the auxiliary cross-linking agent, which is also in line with the auxiliary cross-linking agent in actual applications. situation; comparing Example 1 and Example 10 (the different amounts of cross-linking agent added are due to the differences in the amounts of different types of cross-linking agents used, and here the two samples have the same thermal elongation, both 40%) it can be seen that different cross-linking agents have different scorch resistance, and the scorch resistance of the BIPB cross-linking agent is much better than that of the DCP, which is also consistent with the difference in activation energy between the two mentioned above; comparing Example 6 and Example 9 it can be seen that when the other additives are the same, after the cross-linking agents DCP and BIPB are replaced in equal proportions, the scorch resistance of the sample with BIPB added is better than that of the pure DCP sample; comparing Example 10 and Example 11, it is further illustrated that the addition of the anti-scorch agent makes the material more scorch-resistant.
[0067] It can be seen that the method provided by the present invention can intuitively measure the scorch resistance of peroxide cross-linked polyethylene. At the same time, the testing method principle of the present invention is more in line with the actual scorch process of peroxide cross-linked polyethylene insulation in cable processing, that is, constant temperature and basically no shear heat, which makes up for the current situation of the lack of a method for accurately testing the scorch resistance of peroxide cross-linked polyethylene insulation. At the same time, the method of the present invention provides a certain reference value for the scorch performance test of other thermosetting materials.
[0068] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for testing the scorch resistance of peroxide cross-linked polyethylene insulation material, characterized in that: The method comprises: preparing non-crosslinked test samples from peroxide cross-linked polyethylene insulation materials of different formulations, testing the torque-time curve at a specific temperature by a rotorless vulcanizer, establishing a calculation formula for evaluating the anti-scorch performance index, using gel content as a basis for the occurrence of scorch to determine the scorch torque, further determining the scorch point, and determining the scorch time according to the time difference between the minimum torque and the scorch torque, so as to judge the anti-scorch performance of the material.
2. The method for testing the scorch resistance of a peroxide cross-linked polyethylene insulation material according to claim 1, characterized in that: The method is specifically as follows: the test sample is subjected to a heating and melting stage in a rotorless vulcanizer device, and the torque reaches the lowest after complete melting, the lowest torque is recorded as Md, and the time point corresponding to the lowest torque is recorded as the melting point Td. The test sample continues to be heated and gradually cross-linked, and the torque generated in real time on the curve is recorded as the real-time torque Mn, and the change between the real-time torque Mn and the lowest torque Md is recorded as ΔN. The torque starts to rise from the lowest torque Md. When the real-time torque of the curve reaches a certain value, the test is stopped, and the torque of the value is recorded as the scorch torque Ms, that is, the material is scorched under the torque, and the time point corresponding to the scorch torque Ms is recorded as the scorch point Ts, and the torque change from the lowest torque Md to the scorch torque Ms is recorded as ΔM, and the time change between the melting point Td and the scorch point Ts is recorded as the scorch time ΔT, thereby obtaining a formula for calculating ΔM, a formula for calculating ΔT, and a formula for calculating ΔN.
3. The method for testing the scorch resistance of a peroxide cross-linked polyethylene insulation material according to claim 2, characterized in that: The formula is: ΔM=Ms-Md, ΔT=Ts-Td and ΔN=Mn-Md; wherein Md is the minimum torque, Ms is the scorch torque, Ts is the time point corresponding to the scorch torque Ms, and Td is the time point corresponding to the minimum torque.
4. The method for testing the scorch resistance of a peroxide cross-linked polyethylene insulation material according to claim 2, characterized in that: The scorch time ΔT is used to indicate the scorch resistance of peroxide cross-linked polyethylene. The larger the ΔT value, the better the scorch resistance of the material.
5. The method for testing the scorch resistance of a peroxide cross-linked polyethylene insulation material according to claim 2, characterized in that: The scorch torque Ms is the torque when the cross-linking degree of the test material reaches a gel content of 80%.
6. The method for testing the scorch resistance of a peroxide cross-linked polyethylene insulation material according to claim 1, characterized in that: The peroxide cross-linked polyethylene insulation material comprises a base material LDPE, a cross-linking agent and an antioxidant.
7. The method for testing the scorch resistance of a peroxide cross-linked polyethylene insulation material according to claim 6, characterized in that: The peroxide cross-linked polyethylene insulation material also includes an anti-scorch agent or a cross-linking aid.
8. The method for testing the scorch resistance of a peroxide cross-linked polyethylene insulation material according to claim 6, characterized in that: The crosslinking agent is DCP or BIPB.
9. The method for testing the scorch resistance of a peroxide cross-linked polyethylene insulation material according to any one of claims 1 to 8, characterized in that: The test conditions of the rotorless vulcanizer are: mold cavity swing frequency: 1.7 Hz, mold cavity swing amplitude: +0.5° to -0.5°, mold cavity temperature: 135°C, mold cavity gas pressure: 0.6 MPa.